TOWARDS A CRITICISM OF THE BODY IN MUSIC: RECOGNIZING AND REVERSING THE MIND-BODY SPLIT IN TRADITIONAL SCHOLARSHIP - Ramunno, Sandra (My University, 2001)
Since antiquity, the study of Western classical music has been influenced by widespread beliefs in the mind-body split. Rational and idealistic philosophies, such as those expounded by Descartes and Plato, have led prominent music scholars throughout history, including Boethius, Rameau, Hoffmann and Hanslick, to focus almost exclusively on music's so-called relationship with the mind-music's abstract, theoretical, intellectual or left-brain qualities. With the development of the score and the musical work concept in the 19th century, the roles of the composer and performer have become increasingly divided in tennis of mind and body respectively. As a result, current musical studies (history, theory/analysis, aesthetics) continue to focus on the format aspects of the composer's score and the positivistic 'facts' surrounding the composer's career, systematically disregarding the role of the body and interpretation in music making.
Recently, however, some music scholars have taken an interest in studying classical music in terms of the body. Using the writings of 20th-century philosophers which convincingly challenge rationalism both within and outside the field of music, these scholars emphasize the relevance of subjectivity (perspectivism) and the body itself in the pursuit of musical 'knowledge.' Anthony Storr, for example, draws on Nietzsche's philosophies to demonstrate the importance of the physical body in the creation and appreciation of music. Richard Leppert similarly borrows Foucault's theory of the social body to uncover neglected political aspects of the body in musical experience (e.g. gender, sexuality, class, ethnicity) and discover the potential for traditional scholarship's fully rational perspective of music to maintain oppressive social stereotypes.
Consequently, the recent development of a criticism of the body in music has become especially important for feminist music scholars. Susan McClary and Suzanne Cusick have been particularly successful at demonstrating the need for scholarship to develop methods which reflect a deeper understanding of the effects of the mind-body problem on the study and practice of music.
Keywords: Music; Music